Strengthening Immunisation Services in India through Digital Transformation from Co-WIN to U-WIN: A Review - Sunidhi Karol; Meenal M. Thakare (Preventive Medicine: Research & Reviews)
In India, the immunisation programme has made a few technology-dependent advancements. The electronic vaccine intelligence network is to manage the immunisation supply chain and logistics. eVIN ensures the timely and effective distribution of vaccines, contributing to successful immunisation campaigns. The other platform is Co-WIN, which served as the digital backbone for India’s COVID-19 vaccination programme. It facilitates the registration and scheduling of vaccine appointments, tracking of vaccination coverage, monitoring adverse events, enabling a swift and organised response to the pandemic. The U-WIN (universal immunisation) is a comprehensive digital system aligned with the Ayushman Bharat Digital Mission. It connects various key components, including the Healthcare Professional Registry, Healthcare Facility Registry and Ayushman Bharat Health Account. This integrated approach aims to strengthen the Universal Immunisation Programme by leveraging digital technology. Overall, these digital initiatives represent a significant leap in India’s immunisation efforts. They enhance data management, supply chain logistics and healthcare infrastructure while ensuring that the immunisation programme is efficient, accessible and responsive to the needs of the population. This integration of technology and health-care systems is a crucial step toward achieving universal immunisation coverage in the country.